Evaluating and assessing the effectiveness of the bidding process for state-owned entities - Mamekwa K. Kekana; Lethukuthula S. Ngubane (Africa’s Public Service Delivery & Performance Review, 2025)
Background: The effectiveness of the bidding process for state-owned entities (SOEs) in South Africa is crucial for efficient resource allocation and service delivery. It is communal information and the government’s acknowledgement that the existing procurement practices used at SOEs are outdated and are confronted with countless difficulties, including conflicts of interest, corruption, fronting, theft, inflated prices, a lack of standardisation, ineffective processes, and a deficiency of suitable controls.